Smoking and Nutrition - Mlcochová, Mgr. Veronika (Journal of Nutritional Therapeutics, 2013)
Smoking cigarettes is considered as a world-wide problem, which is not only medical, but also social. Addiction to nicotine causes chronic and often relapsed diseases, which are interconnected with many other illnesses and which frequently result in the death. Smoking cigarettes causes not only a disease (which does not occur so often in the case of non-smokers), but it also influences life style of smokers. It has been proved that smokers’ eating behaviour is more risky (they eat more fried food, less vegetables and fruits...), therefore they are more likely to fall ill with the non-infectious mass disease